Comparison of oral ketamine and oral midazolam as sedative agents in pediatric dentistry - Damle S; Gandhi M; Laheri V (Wolters Kluwer Medknow Publications, 2008)
The safe and effective treatment of uncooperative or combative preschool children with extensive dental needs is one of pediatric dentist′s ongoing challenges. The traditional methods of behavior management are no longer acceptable to parents as they are not ready to spare more time for dental treatment of their children. Keeping this in mind, the present study was designed and carried out to evaluate the sedative effects of oral ketamine and oral midazolam prior to general anesthesia. Twenty uncooperative children in the age-group of 2-6 years were selected after thorough medical examination and investigations. Informed consent was obtained from the parent. This was a randomized double-blind study. An anesthesiologist administered either 0.5 mg/kg midazolam or 5 mg/kg ketamine orally. The heart rate, respiratory rate, and oxygen saturation were recorded at regular intervals. The sedation and anxiolysis scores were also recorded. The parents were asked to answer a questionnaire at the follow-up session the next day on the surgical experience of the parent and the child and side effects experienced, if any. When the data was subjected to statistical analysis, it was observed that both drugs resulted in adequate sedation at the end of 30 min, with oral midazolam providing significantly better anxiolysis. The heart rate and respiratory rate were marginally higher with oral ketamine. The questionnaire revealed a better response with oral midazolam; side effects were more prominent with oral ketamine.